Essays on foreign direct investment, regional development and location choice - Silva, Eduardo Polloni (Universidade Federal de São Carlos, 2023)
Brazil is a large emerging economy that attracts numerous foreign investments, although there is no consensus on the effects of these investments or the factors influencing their location choice process. Accordingly, this thesis employs regional-level data to investigate the environmental impacts of Foreign Direct Investment (FDI) on the host municipalities in the State of São Paulo, parting from a sustainable development standpoint. Moreover, a larger dataset covering foreign investments in Brazil is employed to investigate the determinants of these investments from the isomorphic pressure standpoint, and the mimetic behavior of multinational companies and their location choices are evaluated. The results suggest that FDI can be beneficial for the future sustainable development of the State of São Paulo, particularly when these companies operate in high-technology and low-technology sectors. In addition, it is advantageous to receive investments from better-developed regions with stronger institutions. Regarding the location choice process, foreign investors are likely to follow previous recent investments, especially from the same sector. This effect is moderated by these companies' previous international experience, although this effect is stronger when the companies are experienced with the Brazilian context, therefore taking more risk. As such, the results present novel evidence on the effects of FDI and the behavior of multinational companies. Hence, the presented results shine light on important implications for policymakers and future investors.
Estudos sobre investimento estrangeiro direto, desenvolvimento regional e decisões locacionais
Keywords: Investimento estrangeiro direto; Desenvolvimento sustentável; Decisão locacional; Mimetismo; Econometria; Foreign direct investment; Sustainable development; Location choice; Mimicry; Econometrics; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INTERNACIONAL::INVESTIMENTOS INTERNACIONAIS E AJUDA EXTERNA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA::ECONOMIA REGIONAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::ECONOMIA DE TECNOLOGIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA::METODOS E MODELOS MATEMATICOS, ECONOMETRICOS E ESTATISTICOS